Synergistic effect of meropenem and vancomycin antibiotics with Ecballium elaterium and Senna italica extracts - Lubna Abdallah; Hiba Odeh; Huda Salem; Thanaa Barham; Samah Nazzal; Rahaf Kokaly; Hana Sa’d Aldeen; Amal Holuo (Journal of BioScience and Biotechnology)
The aim of this study is to determine whether the use of plant extracts like Ecballium elaterium and Senna italica leaf aqueous extracts helps support the activity of meropenem and vancomycin antibiotics against Staphylococcus aureus and Staphylococcus epidermis bacteria. The minimum inhibitory concentration (MIC) and the fractional inhibitory concentration (FIC) were used to find out the antibacterial effect of E. elaterium and S. italica extracts in combination with meropenem and vancomycin antibiotics by employing microbroth dilution assay and checkerboard assay. According to the obtained results, all combinations showed a synergistic effect against S. aureus except vancomycin and S. italica combinations which exhibited an additive effect. Moreover, all combinations exhibited an additive effect against S. epidermis except vancomycin and E. elatenium, which showed a synergistic effect. In conclusion, E. elaterium and S. italica leaf aqueous extracts have great potential as sources of antibacterial compounds against microorganisms and they can be used to treat infectious diseases caused by antibiotic-resistant microorganisms.